2021
DOI: 10.3390/ijerph182413246
|View full text |Cite
|
Sign up to set email alerts
|

Early Diagnosis of Oral Mucosal Alterations in Smokers and E-Cigarette Users Based on Micronuclei Count: A Cross-Sectional Study among Dental Students

Abstract: The presence of micronuclei in oral epithelial cells is considered a marker of genotoxicity, which can be identified using exfoliative cytology. The aim of this study was to investigate cytotoxic damage through the evaluation of micronuclei in the oral mucosa of smokers and e-cigarette users compared to nonsmokers. We obtained smears from the buccal mucosa of 68 participants divided in 3 groups (smokers, e-cigarette users and nonsmokers), which were further processed with Papanicolaou stain. The frequencies of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 51 publications
(54 reference statements)
1
27
0
Order By: Relevance
“…These counts were also higher in smokers than in nonsmokers. These results are in line with those of several periodontitis studies [11,24,28,29] and smoking studies [9,24,28,30–32] that have reported higher micronuclei counts in exfoliated buccal mucosal epithelial cells of periodontal patients and smokers than in controls, suggesting that periodontitis and smoking may affect baseline micronuclei counts in exfoliated buccal mucosal epithelial cells. For example, Bloching et al [24] observed higher micronuclei counts in exfoliated buccal mucosal epithelial cells in subjects with periodontitis, particularly those with periodontitis who use tobacco.…”
Section: Discussionsupporting
confidence: 91%
“…These counts were also higher in smokers than in nonsmokers. These results are in line with those of several periodontitis studies [11,24,28,29] and smoking studies [9,24,28,30–32] that have reported higher micronuclei counts in exfoliated buccal mucosal epithelial cells of periodontal patients and smokers than in controls, suggesting that periodontitis and smoking may affect baseline micronuclei counts in exfoliated buccal mucosal epithelial cells. For example, Bloching et al [24] observed higher micronuclei counts in exfoliated buccal mucosal epithelial cells in subjects with periodontitis, particularly those with periodontitis who use tobacco.…”
Section: Discussionsupporting
confidence: 91%
“…In previous reports, e-cigarettes were considered less harmful to users as an aid to smoking cessation and a replacement for regular cigarettes 28 , 34 , 35 . Pop et al 36 found that clinically healthy young tobacco smokers and e-cigarette users presented an increased number of micronuclei in the oral epithelial cells, compared to non-smoking individuals. Bardellini et al 37 reported e-cigarette users to have more frequent oral lesions, burns, or inflammation compared to former or non-smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, early detection of OSCC and the screening of all types of PMOLs become crucial in prevention and treatment outcomes [ 123 ]. In order to overcome the problem of early diagnosis, various diagnostic methods for screening have been proposed, such as exfoliative cytology (cytobrush) [ 123 , 124 , 125 ], the use of vital dyes [ 46 ], evaluation of oral mucosa alteration using light emission sources (chemiluminescence and autofluorescence) [ 126 , 127 ] and more recently, molecular biomarkers and salivary assays [ 128 , 129 ], which seemed promising methods, with high potential for becoming diagnostic tests [ 37 ].…”
Section: Difficulties Associated With the Early Diagnosis Of Osccmentioning
confidence: 99%